Law of Contracts in Lex Baiuvariorum - Nótári, Tamás (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
This paper intends to analyse the contractual provisions of Lex Baiuvariorum, the written Bavarian Volksrecht created between 737 and 743. As part of that, first, it will examine the required formalities of entering into a contract, documentary evidence and testimony (I.), then the issues of invalidity (II.), implied warranty and buying stolen things (III.), regulation of contractual safeguards (IV.), finally, other contracts touched upon in the code (V.). Concerning sedes materiae it should be stated in advance that provisions regarding exchange of goods can be found primarily in two titles of the code: title eleven (De venditionibus) and title nine (De furto)—the latter sets out the rules on selling stolen things, i.e., implied warranty claims, which pay regard to the relation between the person who has been robbed and the person who buys the thing in good faith, on the one hand, and between seller and buyer, on the other. Certain provisions, for example, regarding prohibition to sell things in action can be found in title fifteen (De commendatis et commodatis). [1] On Lex Baiuvariorum see Nótári, T.: Lex Baiuvariorum—A bajorok törvénye. Szeged 2011. (Nótári 2011a); Römischrechtliche Elemente im Prolog der Lex Baiuvariorum. Annales Universitatis Scientiarum Budapestinensis de Rolando Eötvös nominatae, Sectio Iuridica 50. 2009. 419–429; Bavarian Historiography in Early Medieval Salzburg. Passau 2010; Personal Status and Social Structure in Early Medieval Bavaria. Acta Juridica Hungarica 50. 2009/1. 85–110; An Early-Medieval „Show Trial”—Tasilo III’s Dethronement. In: Beck Varela, L.–Gutiérrez Vega, P.–Spinosa, A. (eds): Crossing Legal Cultures. München 2009. 141–158. [2] Cf. Beyerle, K.: Lex Baiuvariorum. Lichtdruckwiedergabe der Ingolstädter Handschrift. München 1926; Merkel, J.: Das Bairische Volksrecht. Archiv der Gesellschaft für ältere deutsche Geschichtskunde 11. 1858. 533–687; Schwind, E. v.: Kritische Studien zur Lex Baiuwariorum III. Neues Archiv der Gesellschaft für ältere deutsche Geschichtskunde 37. 1912. 415–451; Krusch, B.: Die Lex Bajuvariorum. Berlin 1924. 38–163; Kottje, R.: Die Lex Baiuvariorum—das Recht der Baiern. In: Mordek, H. (Hrsg.): Überlieferung und Geltung normativer Texte des frühen und hohen Mittelalters. Sigmaringen 1986. 9–23; Eckhardt, K. A.: Die Lex Baiuvariorum. Eine textkritische Studie. Untersuchungen zur deutschen Staats- und Rechtsgeschichte 38. Bresslau 1927; Landau, P.: Die Lex Baiuvariorum: Entstehungszeit, Entstehungsort und Charakter von Bayerns ältester Rechts- und Geschichtsquelle. München 2004. [3] Babják I.: Barbárság vagy germánság? Árucsere Európa hajnalán. Budapest 2011. 175.